The persistence of television: The case of The Good Life. (March 2017) - Bonner, Frances; Jacobs, Jason
We argue here that rather than being threatened by new modes of delivery and of viewing, television persists and that this can be charted by examining the familiarity and recognisability of television across the post-World War II period, looking at British, American and Australian programmes, personalities and practices, including promotion. The article presents a case study of the BBC sitcom The Good Life to show some ways that television persists. It considers the sitcom genre, institutional practices, repeat screenings, particular types of spin-off programmes and the place of the show in the subsequent careers of the main actors.